Online concept-mapping as an innovative tool for assessment of deep learning - Ling, Nicholas Sui Chong; Ma'rof, Aini Marina (Centre for Global Open Access Learning, Immersive Technology & Quality Assurance, Universiti Sains Islam Malaysia, 2017)
Concept mapping is a visual representation of ideas that facilitates thinking and is applicable to many areas of education with noticeable impacts on learning. Literatures show that there is difficulty in using concept maps among higher education students although empirical studies have shown that its use over time enhances students’ personalized learning experience. This enable better analysis and synthesis of complicated topics which in turn promotes deep learning. Recent development shows the change from using traditional paper methods to the computer-assisted concept maps which are more flexible and less constrained. The present study explored the using of the computer-based/online concept mapping and enrich background image to promote conceptual understanding of undergraduate students in the Thinking Skills subject. A total of 50 first year students majoring in Mathematics and Statistics participated in this study. We conclude that online concept-mapping is a scalable and implementable tool for teaching in higher education, in that it helps cater the different learning styles of students, enhances their metacognitive skills and promotes greater conceptual understanding of the concepts learned.